(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In the recent year Mobile Adhoc Networks [MANET] have been widely researched for many years. Mobile Adhoc Networks are a collection of two or more devices equipped with wireless communication and networking capabilities without infrastructure. The majority of applications are in areas where rapid deployment and dynamic reconfiguration are necessary and a wire link network is not available. The node should deploy an intermediate node to be the router to route the packet from the source toward the destination. The Mobile Adhoc Network do not have gateway because every node can act as the gateway. The traditional protocol such as TCP/IP has limited use in Mobile Adhoc Networks because of the lack of mobility and resources. In this paper survey on the current status and direction of research on Mobile Adhoc Network. Â Keywords:â€” Adhoc Networks, MANET, Routing Protocols, Energy Efficient, Security.